2011
DOI: 10.1021/nn202710s
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Holey Graphene Paper Electrodes with Enhanced Rate Capability for Energy Storage Applications

Abstract: The unique combination of high surface area, high electrical conductivity and robust mechanical integrity has attracted great interest in the use of graphene sheets for future electronics applications. Their potential applications for high-power energy storage devices, however, are restricted by the accessible volume, which may be only a fraction of the physical volume, a consequence of the compact geometry of the stack and the ion mobility. Here we demonstrated that remarkably enhanced power delivery can be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
348
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(362 citation statements)
references
References 63 publications
(85 reference statements)
11
348
1
2
Order By: Relevance
“…However, the steep delithiation voltage profi les, together with the high 1 st cycle irreversible capacity, left few chances for its practical application. A further approach was reported by H. H. Kung et al, [ 60 ] who introduced in-plane carbon vacancies into the graphene structure, to produce a fl exible defect-rich RGO paper named "holey graphene". When used as Li-ion host, the holey graphene could sustain massive current loads (i.e., 10 A g −1 ) providing reasonable reversible capacity values (i.e., about 75 mAh g −1 ).…”
Section: Continuedmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the steep delithiation voltage profi les, together with the high 1 st cycle irreversible capacity, left few chances for its practical application. A further approach was reported by H. H. Kung et al, [ 60 ] who introduced in-plane carbon vacancies into the graphene structure, to produce a fl exible defect-rich RGO paper named "holey graphene". When used as Li-ion host, the holey graphene could sustain massive current loads (i.e., 10 A g −1 ) providing reasonable reversible capacity values (i.e., about 75 mAh g −1 ).…”
Section: Continuedmentioning
confidence: 99%
“…Additionally, once again, the authors calculated power and energy densities of a single electrode and improperly compared the obtained values, with other electrochemical energy storage technologies. [ 60 ] Despite previous papers claimed a certain fragility of bare RGO paper electrodes, [ 35 ] these last two research efforts clearly demonstrated that the introduction of defects, or the direct functionalization of RGO's surface with other electroactive species, could enable fl exible graphene-based electrodes. Similarly, other research efforts on N-doped RGO [ 61 ] and RGO paper functionalized with CNT [ 62,63 ] were reported, but no substantial improvement in terms of electrochemical performance could be observed (Table 1 ).…”
Section: Continuedmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on Li-ion batteries have shown that 2-D layered nanomaterials such as graphene and transition metal dichalcogenides (TMDCs such MoS 2 , WS 2 ) are promising materials for efficient storage and release of Li-ions. [26][27][28][29][30][31][32][33][34][35][36][37] However, when compared with graphite, the electrochemical lithiation in layered TMDCs is distinct as majority of the lithium is stored by means of a conversion reaction in which Liion reacts with the TMDC forming Li 2 S and transition metal phases as the reaction products. More important, this type of a conversion reaction can allow transfer of 2 to 6 electrons per transition metal compared to single electron in the case of intercalation reaction (lithium/carbon system).…”
mentioning
confidence: 99%
“…Several key characteristics of LIB performancenamely, reversible capacity, voltage, and energy density -are ultimately determined by the binding between Li and the electrode material [1][2][3]. Graphite has long been used commercially as a LIB anode, and recently, defective graphene and other sp 2 C derivatives have shown promise as high-capacity and high-power anodes [4][5][6][7][8][9][10][11][12]. However, these seemingly similar substrates exhibit a wide range of Li-C binding energies.…”
mentioning
confidence: 99%